Enforcement vs. access: wrestling with intellectual property on the internet - Sebastian Haunss (Internet Policy Review, 2013)
Politicisation of intellectual property, driven by the digitisation of media and the rapid expansion of the internet, has made intellectual property rights relevant not only for a limited number of corporate actors, but increasingly for individual citizens in their everyday practices. The article assesses the current state of intellectual property politics and draws attention to three parallel processes: 1) the growing focus on enforcement, 2) the plurilateralisation of international intellectual property policies, and 3) the trend towards open access. The regional focus of this analysis is on Europe, but similar trends are visible in the US as well.
Keywords: 300; Anti-Counterfeiting Trade Agreement (ACTA); Intellectual property; Copyright; Content; Academic publication; Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS); Free trade agreements; Intellectual Property Rights Enforcement Directive (IPRED); Digital rights management (DRM)